Kajian Bentuk dan Kesesuaian Gerak Patung Legenda Danau Toba terhadap Cerita Legenda Danau Toba - Joy Endiko Manik; Tetty Mirwa (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to describe the shape and suitability of the statue's motion to the legendary story of Lake Toba in Siallagan village. The method used in this research is descriptive qualitative. The population in this study were ten human statues in the Taman Wisata Legenda Danau Toba which consisted of 10 statues. The 10 statues were assessed to get answers about the shape and suitability of body movements with the Legendary Story of Lake Toba in Siallagan Village. The highest value of a statue has an average value of 73, namely the 2nd sculpture work.While the lowest score of the statue has an average value of 57.25, is the 6th statue work. which is large enough from the beginning of the story to the illustration of the last goldfish statue depicting the end of the story that Uli returned to being a goldfish and the whole village sank to form a lake and an island.